2012
DOI: 10.1590/s1809-29502012000300013
|View full text |Cite
|
Sign up to set email alerts
|

Influência da informação sensorial adicional no treinamento sensório-motor

Abstract: O objetivo deste estudo foi investigar o efeito do treinamento sensório-motor, com e sem a utilização de informação sensorial adicional do tipo tira subpatelar, no controle postural de indivíduos sadios. Trinta adultos jovens e sadios participaram deste estudo, divididos aleatoriamente em três grupos: controle (GC), experimental sem informação sensorial adicional (GE) e experimental com informação sensorial adicional (GEI). Os participantes realizaram a tarefa de apoio monopodal, com olhos fechados, sobre uma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…The mechanism of the sensory information addition action, especially the subpatellar strip, has not yet been fully elucidated. The main hypothesis, found in studies, suggests the increase of afferents by constant cutaneous stimulation, greater stimulation to the superficial skin receptors and local receptors, with consequent improvement of the articular proprioceptive response (12)(13)(14)(15)(16)22) . Older fallers present reduced mobility and are more likely to decrease muscle strength caused by aging and inactivity, with consequent impact on walking and stabilization of the ankle and hip (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of the sensory information addition action, especially the subpatellar strip, has not yet been fully elucidated. The main hypothesis, found in studies, suggests the increase of afferents by constant cutaneous stimulation, greater stimulation to the superficial skin receptors and local receptors, with consequent improvement of the articular proprioceptive response (12)(13)(14)(15)(16)22) . Older fallers present reduced mobility and are more likely to decrease muscle strength caused by aging and inactivity, with consequent impact on walking and stabilization of the ankle and hip (36).…”
Section: Discussionmentioning
confidence: 99%
“…One of the forces that maintain postural control is sensory information, interfering with motor action related to postural control, and it is influenced by motor actions (9)(10)(11) . Some studies have indicated that sensory information can be used continuously in individuals with proprioceptive deficit with good results in reducing body oscillation and improving mobility (8)(9)(10)(11)(12)(13)(14) . The first studies by Bonfim and Barela (11) , showed the body oscillation reduction in a situation of contact with a touch bar in individuals who had lesions of anterior cruciate ligament (ACL).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, sensory information is connected to motor action and vice versa. Increase of sensory stimuli could reduce the body oscillation, keeping the body in a particular position and improving balance 7 . Some studies have investigated the use of sensory information in body balance using a soft touch on a rigid and stationary surface, and the results obtained showed a significant reduction in body oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…Towards this, additional sensory information can be used continuously for body oscillation reduction 4,[8][9][10] . Thus, an increase of proprioception, balance, and postural control can be obtained by the infrapatellar bandage mechanism 4,7,11,12 , increasing motor control organization, which may lead to a decrease in body oscillation 13 . Despite the positive effects of the use of additional sensory information in the postural control [8][9][10] , there is still no evidence of the contribution of this additional information in a more dynamic process, such as the gait.…”
Section: Introductionmentioning
confidence: 99%
“…A falta de controle visual para autocorreção leva a um reajuste do sistema nervoso central através de outros sistemas 7,8 que são suscetíveis a estimulação, sabendo-se da capacidade de adaptação do sistema nervoso por meio de experiências e atividades, espera-se que o equilíbrio corporal e coordenação motora adequados possam ser alcançados a partir de um treinamento relacionando informação sensorial e ação motora, como no treino sensório-motor 9,10 .…”
unclassified